Multikultural Issues In Guidance and Counseling: A Bibliometric Approach To Publication Trend Analysis - Nasution, Salsabila; Karneli, Yeni; Netrawati; Ifdil (Universitas Negeri Medan, 2025)
Multicultural education continues to develop around the world, including Indonesia. This study describes multikultural education from various perspectives, including an overview of multicultural education publications; trends; countries; researchers; and future hotspots for multicultural education, both internationally and in Indonesia. This study is a qualitative research using bibliometric analysis following the framework developed by (Garza-Reyes), with the data for this document analysis sourced from Scopus using three search criteria. The findings reveal that interest in this topic is increasing, particularly with the significant number of studies published in 2024, reaching a peak of 196 publications. Many countries and authors have contributed to research on multicultural issues. Therefore, the challenges and opportunities in multicultural education require a holistic approach, involving collaboration between parents, teachers, and educational policies to create a fair and inclusive learning environment for all students.